2011
DOI: 10.1258/ijsa.2011.011236
|View full text |Cite
|
Sign up to set email alerts
|

HIV-testing of men who have sex with men: variable testing rates among clinicians

Abstract: High HIV testing coverage of high-risk populations is required to reduce the number of HIV-infected individuals unaware of their status. The aim of this study was to determine HIV testing rates among men who have sex with men (MSM) attending a sexual health service, including the impact of the treating clinician on HIV testing rates. Factors associated with HIV testing of MSM attending the Melbourne Sexual Health Centre for the first time between 2003 and 2009 were determined, including testing rates for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Australian studies have also shown variable rates of test offer between individual clinicians. 19 These findings have identified that targeting tests to selected patients has a negative impact on patients' acceptance of tests. The comfort of staff with offering tests and managing reactive results was assessed in a third pilot, with 63% (range 57-75%) of staff anticipating discomfort prior to the testing phase; following the pilot, however, staff reported high levels of satisfaction and no negative impacts on the department.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Australian studies have also shown variable rates of test offer between individual clinicians. 19 These findings have identified that targeting tests to selected patients has a negative impact on patients' acceptance of tests. The comfort of staff with offering tests and managing reactive results was assessed in a third pilot, with 63% (range 57-75%) of staff anticipating discomfort prior to the testing phase; following the pilot, however, staff reported high levels of satisfaction and no negative impacts on the department.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In the USA, the uptake of HIV testing at the time of STI diagnosis/treatment among MSM with bacterial STIs was significantly increased from 62% to 76% following an intervention where all MSM diagnosed with STIs and their partners were offered HIV testing [54]. Fourth, involving nurses in conducting HIV tests and providing HIV chronic disease care and education could increase HIV testing uptake among STI clients [44, 45, 55]. In Australia, HIV testing rates amongst HIV negative MSM significantly increased from 41% to 47% after an STI nurse was introduced into general practice clinics [56].…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, there were several situations where concurrent HIV/STI testing was high. First, it was high in studies using the routine offer of HIV testing amongst STI clients [25,[44][45][46]. Routine offer of HIV testing in antenatal settings has been implemented successfully in many countries for more than a decade [47,48].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…While this may reflect patients' personal risks, knowledge and beliefs, there is evidence that testing rates are highly dependent upon practitioner-related factors and thus may be increased through clinic-based quality improvement programmes. 14 At present, the number of studies investigating the compliance with international protocols is surprisingly low. One UK-based study found that only 14% of high-risk individuals were offered an HIV test at a sexual health clinic.…”
Section: Discussionmentioning
confidence: 99%